Freedom of Expression Under The Jordanian Legal System - Ahmed Toubat, Hazem Suleiman; Halim, Rohizan; Mohamed Yusoff, Zuryati (Medwell Publications, 2017)
Jordanian Constitution provides for freedom of expression and entrusts to the legislative, executive, and judicial powers to ensure this right for all Jordanians. It also authorizes the legislature to regulate practicing the rights and freedoms provided that it does not affect the essence of these rights. The legislature has enacted several laws which include limitations on freedom of expression, most notably; the Penal Code of 1960, the Press and Publication Law of 1998 and Anti-Terrorism Law of 2006. This paper aims to examine the freedom of expression under the Jordanian Constitution and the limitations on this freedom in the laws that mentioned. The doctrinal approach is conducted and the data is collected through legal and constitutional texts as well as the secondary sources that illustrate the contribution of other researchers in this area. This paper concludes that the laws which regulate freedom of expression in Jordan have expanded the scope of limitations and the scope of protected interests. It recommends a comprehensive review of the laws governing freedom of expression and amending them in order to comply with the provisions of the Jordanian Constitution